2018
DOI: 10.1038/s41588-018-0102-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors operate across disease loci, with EBNA2 implicated in autoimmunity

Abstract: Explaining the genetics of many diseases is challenging because most associations localize to incompletely characterized regulatory regions. We show that transcription factors (TFs) occupy multiple loci of individual complex genetic disorders using novel computational methods. Application to 213 phenotypes and 1,544 TF binding datasets identifies 2,264 relationships between hundreds of TFs and 94 phenotypes, including AR in prostate cancer and GATA3 in breast cancer. Strikingly, nearly half of the systemic lup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
355
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 316 publications
(377 citation statements)
references
References 82 publications
(79 reference statements)
19
355
0
3
Order By: Relevance
“…EBV resides in B lymphocytes of the infected individual in a latent form [25]. In the B lymphocytes, EBV Nuclear Antigen 2 (EBNA2) regulates latent viral transcription which allows immortalization of the virus and recruitment of transcription factors that bind to regions of both the EBV genome and the host’s own genome [9,26]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EBV resides in B lymphocytes of the infected individual in a latent form [25]. In the B lymphocytes, EBV Nuclear Antigen 2 (EBNA2) regulates latent viral transcription which allows immortalization of the virus and recruitment of transcription factors that bind to regions of both the EBV genome and the host’s own genome [9,26]. …”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis is the production of anti-apoptotic signals by EBV, which lead to development of ectopic lymphoid structures rich in infected B cells [29]. The elevated number of infected B cells constitutes a reservoir of antigenic and viral particles contributing to the autoimmune process [9]. In a recent study comparing genetic and protein sampling from healthy individuals and patients with autoimmune diseases, Harley et al identified regulatory gene regions associated with the risk of developing systemic erythematous lupus (SLE) and other autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A paper by Harley et al in Nature Genetics provides an important new perspective on the mechanisms by which infection with Epstein-Barr virus (EBV) can promote autoimmunity and, in particular, systemic lupus erythematosus (SLE) 1. An interest in the role of EBV in lupus pathogenesis has a long history beginning in the 1970s with observations that patients with SLE have increased titres of anti-EBV antibodies 2.…”
mentioning
confidence: 99%
“…Using data from a number of experimental sources, RELI can assess ‘the significance of the interactions of the genomic coordinators of plausibly causal genetic variation and DNA sequences bound by a particular TF, as determined through chromatin immunoprecipitation and sequencing (ChIP-seq)’ 1. The authors first validated this approach with prostate and breast cancer cell lines and then went on to study SLE and other autoimmune diseases, focusing on the interaction of EBNA2 with European ancestry risk alleles.…”
mentioning
confidence: 99%